2013
DOI: 10.4236/ns.2013.53050
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann modeling for tracer test analysis in a fractured Gneiss aquifer

Abstract: Fractured Gneiss aquifers present a challenge to hydrogeologists because of their geological complexity. Interpretation methods which can be applied to porous media cannot be applied to fractured Gneiss aquifers because flow and transport occur in fractures, joints, and conduits. In contrast, the rock matrix contribution to groundwater flow is not very important in Gneiss aquifers. Sodium chloride was injected into groundwater flow under steady state condition as tracer to determine transport parameters which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The critical value can be determined by |2/ sqrt (n) | where n is the number of observations. Compared with previous work done by Abdelaziz et al (2013), where Lattice Boltzmann was implemented for the same case, we found that the use of UCODE delivered a significant enhancement in the calculated concentration values. For that reason, using a local optimizer like UCODE2013 essential is required for understanding the coupled 235 flow and solute transport mechanism in fractured gneiss aquifer…”
supporting
confidence: 40%
See 1 more Smart Citation
“…The critical value can be determined by |2/ sqrt (n) | where n is the number of observations. Compared with previous work done by Abdelaziz et al (2013), where Lattice Boltzmann was implemented for the same case, we found that the use of UCODE delivered a significant enhancement in the calculated concentration values. For that reason, using a local optimizer like UCODE2013 essential is required for understanding the coupled 235 flow and solute transport mechanism in fractured gneiss aquifer…”
supporting
confidence: 40%
“…A tracer solution was injected under steady-state conditions, over a period of 6.5 hours into the observation well 4, while concentrations were recorded as a depth-integrated breakthrough curve 165 at the observation well 6. Further information and details about the tests, technical details, and solute analysis are provided in(Abdelaziz and Merkel, 2012;Abdelaziz et al, 2013;Abdelaziz and Zambrano-Bigiarini, 2014) Model SetupA three dimensional finite difference scheme was used to simulate the experimental area. The model consists of three layers (Figure 2).…”
mentioning
confidence: 99%
“…In our experiments, a tracer solution was injected under steady-state conditions, over a period of 6.5 hours into the observation well 4, while concentrations were recorded as depth-integrated breakthrough curve at the monitoring well 6 (see Figure 1). Further information and technical details about the tests and solute analysis are provided in Abdelaziz and Merkel (2012) and Abdelaziz et al (2013).…”
Section: Tracer Testsmentioning
confidence: 99%
“…One of the wells was drilled to a depth of 100 m and 5 wells to a depth of 50 m. The upper part of the boreholes (3 to 5 m) is protected by a steel stand pipe; the deeper part was left as open borehole. A major horizontal fracture zone was determined to be 11 m below the ground surface by geophysical and hydraulic tests (Abdelaziz and Merkel, 2012;Abdelaziz et al, 2013), while Packer tests, geophysical logs, and tracer tests were conducted in the test field. …”
Section: Study Areamentioning
confidence: 99%
“…Owing to the bed rocks having complex geological conditions and developed faults and fissures, seepage within the fractured rock mass of the dam foundation has a significant impact on the safe operation of the dam. It is a challenge to investigate and model a fractured flow [4][5][6]. Therefore, statistical techniques, e.g., Monte Carlo simulations, random field theory, and the finite element technique, have been employed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%